2020
DOI: 10.1038/s41398-019-0665-5
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Differential transcriptional response following glucocorticoid activation in cultured blood immune cells: a novel approach to PTSD biomarker development

Abstract: This Article was originally published without the correct Supplemental Table file (Table S1 was missing). In total, there are seven Supplemental Tables, and six were in the original submission. Furthermore, Fig. 1 was misplaced in the main text; it was embedded in the manuscript file even before the results section. Both issues have now been fixed in the HTML and PDF versions of this Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
239
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(265 citation statements)
references
References 0 publications
24
239
2
Order By: Relevance
“…In terms of worries about COVID-19, parents in our sample reported being most worried about a family member getting the virus, unknowingly spreading the virus, and getting the virus themselves. Our results align with a prior study of adults ( N = 3042) recruited via online crowd-sourcing, where concerns about a family member getting the virus and unknowingly spreading the virus were similarly ranked as the top two concerns [ 54 ]. These findings are also consistent with prior evidence of increases in prosocial and “tend-and-befriend” responses during times of stress, thought to reflect an innate human tendency to protect those closest to them and seek out their social group when threatened [ 64 , 65 ], which appears to be especially the case among females and female caregivers [ 54 , 66 ], as was the case for the vast majority of parents in our sample.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In terms of worries about COVID-19, parents in our sample reported being most worried about a family member getting the virus, unknowingly spreading the virus, and getting the virus themselves. Our results align with a prior study of adults ( N = 3042) recruited via online crowd-sourcing, where concerns about a family member getting the virus and unknowingly spreading the virus were similarly ranked as the top two concerns [ 54 ]. These findings are also consistent with prior evidence of increases in prosocial and “tend-and-befriend” responses during times of stress, thought to reflect an innate human tendency to protect those closest to them and seek out their social group when threatened [ 64 , 65 ], which appears to be especially the case among females and female caregivers [ 54 , 66 ], as was the case for the vast majority of parents in our sample.…”
Section: Discussionsupporting
confidence: 89%
“…Parents answered five questions about their exposure to COVID-19, including whether they had been tested, experienced symptoms, knew someone who tested positive, knew someone who died, and whether their job was impacted [ 54 ]. Answers for two questions were collapsed to create meaningful binary outcomes: tested for COVID-19 combined any testing (i.e., being tested and whether parents ultimately tested negative or positive) and negative impact on job combined any change in job, income, or hours (i.e., losing job, reduced hours, or reduced pay) (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another review and meta-analysis on the mental health impact of COVID-19 on health care professionals reported that anxiety, depression, and anxiety, was prevalent in 23·2%, 22·8%, and 38·9% of the study participants respectively [ 14 ]. Multiple earlier studies reported the prevalence of generalized anxiety symptoms, and depressive symptoms among the general population during the COVID-19 period were 35.1%, and 20.1% in China [ 15 ], 23.6% and 45.1% in turkey [ 16 ], 65% and 69% in Pennsylvania [ 17 ].…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Besides, Shanafelt [ 11 ] found increased personal wellbeing in medical residents with higher levels of empathy. Empirical research shows that it is essential to work effectively with others in suffering, contribute to the development of a strong therapeutic relationship, and correlate with better clinical outcomes [ 4 , 12 ]. Furthermore, developing empathy is necessary to become professionally competent and have higher professional fulfilment [ 13 ].…”
Section: Introductionmentioning
confidence: 99%